High-Precision Calibration of Phase-Only Spatial Light Modulators - Yicheng Zhao (IEEE, 2022)
In the fields of optics and photonics, phase-only spatial light modulators (SLMs) play an increasingly important role in wave-front engineering. However, the SLMs are subject to wavefront distortion arising from the imperfection in the birefringence effect and physical structure of modulators. This paper presents a simple self-interference phase calibration method applicable to liquid-crystal SLM. We build an interferometric imaging system based on the Pancharatnam phase-shifting to measure the phase distribution of a light beam coming from SLMs. Two types of phase modulation errors of SLMs can be characterized in the measurement process: the erroneous gamma curve and shape aberration. The former belongs to dynamic phase distortion and is measured through a four-step Pancharatnam phase-shifting interference, which allows a one-shot recording of interference pattern via a polarization camera; the latter represents static phase distortion and is extracted from the interference between light waves coming from different regions of the SLM panel by using Zernike polynomial fitting. Our method has the advantages of high-precision pixel-wise phase correction and robustness against environmental disturbance and thus can facilitate the applications of SLM in optical field manipulation.